The Crucial Role of Third Body in Formation and Evolution of Contact Binary Systems: Evidence from CY Ari and IK Lyn - Hu-Shan Xu; Zhong-Tao Han; Wei-wei Na; Zhi-Hua Wang; Wen-wu Ma; Li-Ying Zhu (The Astrophysical Journal)
CY Ari and IK Lyn are two eclipsing binary systems that share the same spectral type but exhibit significantly different metallicities. Based on the Wilson–Devinney (W-D) method, the first photometric solutions are obtained by analyzing the new complete BVR _c I _c light curves. The completely eclipsing nature of the light curves allows for the determination of reliable photometric parameters for both systems. Analysis of the light curves indicates that the two systems are structurally similar. Both belong to W-type shallow contact binary systems, with nearly identical degrees of contact. The O − C analysis demonstrates that the orbital periods of CY Ari and IK Lyn are increasing over the long term, with the increase rate for IK Lyn being significantly higher than that for CY Ari. This discrepancy may arise from different mass transfer rates from the secondary star to the primary star. Additionally, a periodic oscillation with a period of 5.4 yr has been detected in CY Ari, potentially attributable to the light-time effect of an unseen third body. An analysis of the age and evolutionary stage elucidates the reasons behind the divergent evolutionary paths of CY Ari and IK Lyn. The presence of the third body accelerates the evolution of CY Ari by removing angular momentum from the central binary pair. Although CY Ari was formed later than IK Lyn, it has evolved into a similar stage. This study provides critical evidence of the significant role played by a third body in the formation and evolution of contact binary systems.